Legal analysis of the consequences of the party reform of 2012 - G. G. Aminova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The article analyzes the consequences of the large-scale liberalization of the legislation on political parties, held in 2012. In the author's opinion, on the one hand, this reform led to the creation of a large number of political parties; on the other hand there are negative effects of the reform, in particular, the number of party-spoilers increased. In that context the author proposes a solution to this problem - to establish a special Commission on political competition, which would set a limit of the political parties’ actions.